2017
DOI: 10.1093/eurheartj/ehx504.p3490
|View full text |Cite
|
Sign up to set email alerts
|

P3490Phenotypic specification of endothelial cells in chronic thromboembolic pulmonary hypertension

Abstract: Results: We found that severe OSA could damage cardiac function and aggravate collagen deposition via EndMT. These features were improved by PHD3 overexpression. In vitro, PHD3 overexpression in cultured HUVECs ameliorated OSA-induced EndMT through inactivating HIF-1α and Smad2/3. Conclusion: We conclude that PHD3 overexpression might be beneficial in the prevention of OSA-induced cardiac fibrosis by inhibiting EndMT through inactivating HIF-1α and Smad2/3. Introduction: Endothelial erosion of plaques is the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Furthermore, specific marker genes of fibroblast/smooth muscle cells were identified, such as PDGFRB, COL1A1, and COL3A1, which were significantly enriched for multiple functions associated with smooth muscle cell migration. It has been reported that CTEPH endothelial cells can exhibit pro-fibrotic and pro-inflammatory phenotypes, as demonstrated by the expression of genes (COL1A1 and COL3A1) involved in extracellular matrix production and fibril organization [20]. In addition, PDGF is a potent mitogen for cells of mesenchymal origin, such as fibroblasts and smooth muscle cells [21].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, specific marker genes of fibroblast/smooth muscle cells were identified, such as PDGFRB, COL1A1, and COL3A1, which were significantly enriched for multiple functions associated with smooth muscle cell migration. It has been reported that CTEPH endothelial cells can exhibit pro-fibrotic and pro-inflammatory phenotypes, as demonstrated by the expression of genes (COL1A1 and COL3A1) involved in extracellular matrix production and fibril organization [20]. In addition, PDGF is a potent mitogen for cells of mesenchymal origin, such as fibroblasts and smooth muscle cells [21].…”
Section: Discussionmentioning
confidence: 99%